Gestão democrática da escola pública : a participação da comunidade - Oliveira, Oséias Santos de (2007)
The study places in the scope of discussion that are related to the democratic management of public school, favoring the investigative focus in the relations lived and built through the participation of the educational community. In the beginning it searches for the understanding of the public school emphasizing the role of the agents that are inserted in it students, parents and teachers. The analysis places the educational politics and the legal aspects related to the school in the context of the Teaching System. It also searches for the understanding of the school as its dynamic character, its autonomy and its democratic aspect, being essential to the theoretical basement of analysis the relations of power that carry out in the space of the school. The bibliographic referential explores the habermesiana, perspectives, from the viewpoint of freriana and communicative action, in the concept that favors the dialogic action. Through the methodology of Focus Group, students, teachers, parents of a municipal public school, located in Santa Rosa in the State of Rio Grande do Sul, clear their concepts about the investigated theme. The definition of directions, objectives and school expectations, pass by necessarily through the collective action of thinking and building identity for the public scholar institution, whose possibility is based on democratic exercise. Realizing the analysis of discussion about the importance of the participation and the dialogue in the school, as well as, the imaginary of the educational actors in the context of the school of the dreams, with subjects and significant doings search for elements that make it possible to identify the school as democratic space. The democratic management of the public school is possible and it will be real as the involvement of the educational actors, as the definition of the direction of the school itself as in relation to the ideal citizen to act in the widest context of the society